READING THE MAYOR'S POLITICAL COMMUNICATION: “CITY CELL” AS A MAKASSAR’S IDENTITY - Firdaus Muhammad; Jalaluddin B; Ibnu Hajar (INJECT (Interdisciplinary Journal of Communication), 2023)
Mohammad Ramdhan Pomanto was famous by his agenda of “Lorong Garden” in Makassar. This study revisited the political communication of Pomanto and constructed his long-term political identity through the micro-ecology policy. It applied a qualitative method that used socio-political constructivism as an approach to interpret the phenomenon. This research examined political communication in the context of micro-ecology. Data was collected by interviewing and documenting online news. The research represented Danny Pomanto’s political communication that is participative, progressive, and context then constructed a political memory network that represents his political identity as Makassar's current Mayor. This program or so-called a city cell, reconstructed the structure of the Makassar people's attitude on the notion of alleyways and handled numerous social problems frequently encountered in alley regions.